Two Attempted Retro-Priming Replications Show Theory-Relevant Anomalous Connectivity - Bierman, Dick (Journal of Scientific Exploration, 2019)
We report a theory-relevant post hoc analysis of 2 Dutch retro-priming experiments that were part of a large replication project of the retro-priming experiment by Bem and colleagues. This replication project sought to investigate the role of the experimenter in psi studies. The results of the retro-priming experiments performed by student research groups at the University of Amsterdam (N=61) and of the University Groningen (N=222) however did not replicate Bem’s earlier findings of an anomalous interference of a future stimulus on response times. We report the results of these two studies here, but the over-all results will be reported elsewhere. Both Dutch studies used the exact same software as Bem and colleagues. However, both studies used different questionnaires. The questionnaires asked for information that in previous research had been associated with success in psi tasks and could help us to deal with individual differences but, above all, could be used as selection criteria for participants in future studies. In the Amsterdam study, there were 14 questions, while in the Groningen there were 55. A correlation analysis revealed several significant correlations between the psi-effect in the Bem task and questionnaire items. In this paper we focus on the post-hoc research question: Is this global composition of the correlation matrix anomalous, as suggested by Generalized Quantum Theory? Rather than using the subjective number of ‘significant’ correlations as a dependent variable, we introduced 2 objective measures directly representing the correlation values in the cells to characterize the ‘Connectivity’ in the matrix. Our analysis revealed ‘Connectivity’ to be marginally significant larger (p<0.075) in Groningen and significantly larger in the Amsterdam study (p<0.025). These results are discussed in the framework of the ‘Consciousness Induced Restoration of Time-symmetry’ (CIRTS) and ‘Generalized Quantum Theory’ (GQT) that predict that as soon as there are reasons to expect replicability (or control) the extra chance psi scores will disappear or reverse. The conclusion is that these results can be seen as support, though statistically not strong, for the GQT.